The implication of microplastic contamination on chemical properties of Inceptisols in the horticultural production center of Banuhampu, Agam, West Sumatra, Indonesia - Herviyanti, Herviyanti; Tanjung, Ellsya Tatalia Augustin Putri; Rezki, Dewi; Maulana, Amsar; Darusman, Darusman; Darfis, Irwan; Purwanto, Benito Heru; Prasetyo, Teguh Budi (Journal of Degraded and Mining Lands Management, 2024)
The accumulation of microplastics (MPs) in agricultural land may threaten food security and farmers' health, which is of interest. This study examined the implication of MPs contamination/pollution on the chemical properties of an Inceptisol on different slopes in the horticultural production center of Banuhampu Subdistrict, Agam District, West Sumatra Province. The soil samples were determined by purposive random sampling with a quantitative survey method. Sample testing was carried out using a randomized completely block design with five treatments, i.e., 25-45% in forests, and 0-8%, 8-15%, 15-25%, and 25-45% in fields at a depth of 0-20 cm. The Inceptisol contaminated with MPs has the following characteristics: pH = 5.01, EC = 0.09 dS m-1, Eh = 92.97 mV, mineral = 68.81%, OM = 31.19%, CEC = 60.67 cmol(+) kg-1, C = 2.13%, N = 0.81%, P2O5 = 6.46 ppm, K = 0.48, Ca = 1.59 cmol(+) kg-1, Mg = 0.62 cmol(+) kg-1 , and SO4 = 98.98 ppm. The concentration of MPs on the Inceptisol was 438.33 particles kg-1 with filament shape, transparent color, and large size (1-5 mm) were the most commonly found. Polymer types included polyamide 6, polystyrene, and polyethylene. The effect of slope level on the surface change charger of Inceptisols contaminated with MPs was insignificant. However, the effect was significant in OC, total N, K-exch, and available S. The implications of microplastic contamination/pollution did not have a significant relationship with the chemical properties of the soil. However, it has a negative relationship to redox potential (Eh), mineral composition, and Ca-exch.